The effects of listening exposure in english learners’ speaking skill among students from children Program, level 7, Sections “A” and “B”, from CENIUES, San Salvador, 2015 - Alvarez Rodríguez, Lorena Raquel; Girón Pleitez, Helen Susana; Vides de Guzmán, Claudia Marina; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
The English language is one of the most dominant languages throughout the world; for that reason, in many cases it is necessary to speak English to have better life conditions such as a better job, education, goods, etc. one of the most common issues that people tend to have while learning English is that they are not capable of producing the language orally; some English learners are able to understand the spoken language, but when they are asked to have an English conversation they failed because they have not developed the speaking skill. Therefore, the present research project aims to determine the effects of listening exposure in English learners’ speaking skill among students from children program, level 7 sections “A” and “B”, from CENIUES, San Salvador, 2015. The researchers focused on planning and teaching the listening activities such as videos, songs, games, etc. to exposed students to the target language. This study focused on how using listening activities in the classroom helps student develop the target language, specifically students’ speaking skill. The research team focused the study based on Stephen Krashen’s theories about the Acquisition Learning Hypothesis, the Input and Output hypothesis, the Direct Method, and Tracy Terrel’s Natural Approach. Besides that, the researchers explain the importance of planning and implementing listening activities in the classroom to build students’ confidence at the time to speak English. Additionally, the researchers have taken into account that nowadays, technology can be useful to teach English, an English teacher can take advantage of it to develop a class; therefore, there are a lot of useful materials that can be found in internet that can help teachers to develop the class, so the research team wants to increase English teachers’ awareness of searching on the net, because the variety of activities that can be found here are very helpful to motivate and to increase student’s confidence too. This research was implemented to improve students’ speaking skill by being exposed to listening activities, so it can be said that this research will provide benefits to the children’s program, the English teachers, students, and the research team.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2016.
Bibliografía : hojas 93-94
Audiencia general.